Estudo de pré-tratamento de bagaço de cana pela associação do ɣ-valerolactona (GVL) e glicerol visando a sacarificação - Amorim, Fausto Rodrigues de (2018)
The rapid consumption of fossil fuels, coupled with the environmental problems attributed to them, and the growing demand for energy have driven the search for renewable energies. Biomass appears as the most viable alternative, but its recalcitrant characteristic requires a pre-treatment, whose prominence points to those using organic solvents (organosolv). This work aimed to evaluate the effects of the association of ɣ-valerolactone (GVL) with glycerol in the pre-treatment of sugarcane bagasse in order to improve saccharification. The experiments were carried out in seven different pretreatment conditions varying the GVL and glycerol proportions in the reaction solution: 80%GVL/0%Gly, 70%GVL/10%Gly, 60%GVL/20%Gly, 50%GVL/30%Gly, 40%GVL/40%Gly, 20%GVL/60%Gly, 0%GVL/80%Gly. After the biomass of the sugarcane bagasse was pretreated, acid hydrolysis, enzymatic hydrolysis analyzes were performed to verify the availability of fermentable sugars (glucose and xylose) and fermentation inhibiting byproducts (furfural and hydroxymethylfurfural). In addition, the recovery of the solvent GVL and the sugars in the solvent and aqueous phase formed after the induction of biphasic hydrolysis solution was verified. The structural alteration of the solid biomass after pretreatment was also analyzed using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction and SEM-scanning electron microscopy techniques. The results of the composition and recovery of biomass, digestibility and glucose yield showed in general that the best results were found in the pre-treatments with higher GVL percentages (60, 70 and 80%). The GVL solvent recovery also showed better results in the pre-treatments with higher solvent percentages (60, 70 and 80%) and their distribution was concentrated in the solvent phase of the biphasic solution, reaching 77% recovery. The glucose distribution was 100% in the aqueous phase in all pre-treatments and xylose, although it appeared in the solvent phase, was concentrated in the aqueous phase with results ranging from 70 to 87%. FT-IR spectra showed peaks at wavelengths 2,915, 1726, 1606, 1507, 1230 and 833 cm -1. All identified bands characterize the removal of lignin by pre-treatments, except for the first one that is related to cellulose and / or hemicellulose. SEM images are congruent with FT-IR results as they show that the lignin and hemicellulose coating on the cellulose fibers were removed to a greater or lesser extent according to each pretreatment. The crystallinity index, calculated by XRD, showed that the crystallinity of the pretreated biomass decreased when compared to the biomass without pre-treatment. With these results, it can be concluded that the association of GVL to glycerol favored the increase of glucose digestibility by up to 8.3 times when compared to bagasse without pre-treatment. The FT-IR, DRX and MEV techniques were able to show that the GVL / Gli pretreatment generated changes in the fibers and crystalline state of the pretreated bagasse. And that the GVL can be recovered in proportions higher than 74% without the distillation thereof in the aqueous phase.